All from one : a guide to Proclus - Hoine, Pieter d'; Hoine, Pieter d'; Martjin, Marije; Martjin, Marije (Oxford University Press, 2017)
Proclus (412-485 A.D.) was one of the last great philosophers of Antiquity. His legacy in the cultural history of the west can hardly be overestimated. This work is the most comprehensive guide to Proclus' life, thought and legacy that is currently available